2008
DOI: 10.1143/jjap.47.2915
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Optic Effect in Amorphous Bi3Fe5O12 Waveguides Sputtered at Room Temperature

Abstract: The intrasubband transition rates of bound carriers interacting with piezoelectric and polar optical phonons in a bulk GaN lattice are presented, considering the anisotropy of the uniaxial wurtzite structure. The directional dependence of the excitonic Bohr radius has a measurable effect for both types of piezoelectric and polar optical phonon scattering. In the latter case, the anisotropy of the uniaxial crystal induces exciton scattering involving both strongly mixed transverse-like and longitudinal-like pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We previously formed a BIG film by magnetron sputtering. 17) However, it was found that the reproducible control of its stoichiometry is not easy because BIG is composed of elements with largely different masses. Thus, we employed a metal organic decomposition (MOD) method this time.…”
Section: Formation and Evaluation Of Magneto-optical Materials Bigmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously formed a BIG film by magnetron sputtering. 17) However, it was found that the reproducible control of its stoichiometry is not easy because BIG is composed of elements with largely different masses. Thus, we employed a metal organic decomposition (MOD) method this time.…”
Section: Formation and Evaluation Of Magneto-optical Materials Bigmentioning
confidence: 99%
“…In Table I, the performance characteristics of several types of optical switches are compared. 15,17,18) Our proposed device operates at a very low voltage less than 100 mV using a copper coil and relatively small power consumption is estimated especially for the PhC device because the volume of the PhC resonator is very small. Here, the switching energies of the PhC and Si ring resonator switches shown in Table I were calculated from the volume of the resonator and magnetization reversal energy density.…”
Section: Introductionmentioning
confidence: 99%